Use of the sugar cane bagasse (Saccharum Officinarum) for the preparation of biodegradable food packages - Barinotto Valencia, Renzo Martin (2024)
Nowadays, sugarcane bagasse is obtained as waste from the sugar industry where it is commonly discarded or burned. Nevertheless, this byproduct contains properties that can be used in the packaging industry. The purpose of this scientific article is to analyze the attributes of small films based on sugarcane bagasse to determine their suitability so that with this data they can produce biodegradable packaging. The most notable results of the tests carried out were the Shore hardness level of 85% of dose 1 and a resistance to elongation of 31.58% of dose 2. With this, added value will be achieved to the sugarcane bagasse since use as raw material in the manufacture of products that provide good to the community. The work carried out has a quantitative approach, descriptive method, and techniques such as observation, documentary analysis and analysis of processes and activities were used.